2015
DOI: 10.1590/0100-3984.2014.0021
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computed tomography in the preoperative staging of gastric adenocarcinoma

Abstract: ObjectiveTo evaluate the role of multidetector computed tomography in the preoperative investigation of tumor invasion depth and lymph node and metastatic involvement according to the TNM classification, in patients with gastric adenocarcinoma.Materials and MethodsFifty-four patients with biopsy-confirmed gastric cancer underwent preoperative staging with 64-channel multidetector computed tomography. Two independent radiologists analyzed the images and classified the findings. Sensitivity, specificity, accurac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
3
18
1
8
Order By: Relevance
“…Various examination methods have limitations in the diagnosis of gastric lymph node metastasis. [21][22][23][24] Figure 4 Gene set enrichment analysis (GSEA) result of FKBP10. (A-C)"KEGG_ADHERENS_JUNCTION","KEGG_ECM_RECEPTOR_INTERACTION","KEGG_FOCAL_ ADHESION","KEGG_GLYCOSAMINOGLYCAN_BIOSYNTHESIS_CHONDROITIN_SULFATE","KEGG_PATHWAYS_IN_CANCER","KEGG_TGF_BETA_SIGNALING_PATH WAY" were enriched in the three independent cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various examination methods have limitations in the diagnosis of gastric lymph node metastasis. [21][22][23][24] Figure 4 Gene set enrichment analysis (GSEA) result of FKBP10. (A-C)"KEGG_ADHERENS_JUNCTION","KEGG_ECM_RECEPTOR_INTERACTION","KEGG_FOCAL_ ADHESION","KEGG_GLYCOSAMINOGLYCAN_BIOSYNTHESIS_CHONDROITIN_SULFATE","KEGG_PATHWAYS_IN_CANCER","KEGG_TGF_BETA_SIGNALING_PATH WAY" were enriched in the three independent cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Various examination methods have limitations in the diagnosis of gastric lymph node metastasis. 21 24 Currently, there are no effective molecular predictors that could be used to predict lymph node metastasis in GC. In this study, we screened out FKBP10 as a potential marker for lymph node metastasis in GC using online data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, gastric tumor enhancement was identified in all patients in the arterial phase, all of them show homogenous enhancement. On MDCT, the extension of tumor load was categorized as follows: T0, no proof of alteration of the gastric wall with even perigastric fat around; T1, infiltration of the gastric mucosa or submucosa [16]; T2, invasion to muscularis propria [17]; T3, invasion to subserosa [16]; and T4, invasion to serosa and adjacent organs or structures [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…However no worldwide consensus exists. Except of size, the other qualitative criteria are applied at the discretion of the radiologist leading to significant intraobserver variability ( 11 ).…”
Section: Computerized Tomographymentioning
confidence: 99%
“…An equilibrium between specificity and sensitivity exists, depending on the selected size threshold. In other words choosing a smaller threshold as pathologic will increase sensitivity at the expense of specificity and vice versa ( 11 ). More or less other criteria suffer from similar limitations.…”
Section: Computerized Tomographymentioning
confidence: 99%